Goat marketing pattern in southern Rajasthan - Pankaj Lavania,; BS Khadda, (Journal of Livestock Biodiversity, 2025)
Livestock marketing plays important role in the economy of farmers, which is generally the most neglected area in the country. It results into strong and pervasive prejudice involvement of middlemen in the market. Sizeable rural populations, especially the economically and socially backward classes, maintain goats and are found in less fertile, arid and semi arid areas of the country. The study revealed that trade is not oligopolistic and farmers did not complain about price fixing. The reason for selling animals is largely financial although sales are made for other reasons also. Majority of the goat farmers in the villages sold their goats to petty traders. However a small percentage of farmers sold their goats directly to rural and semi urban butchers. Goat traders belong mainly to two local groups viz. muslims and khatiks (lower castes). The income from goat rearing was mainly utilized to fulfill the family needs.